1997
DOI: 10.1074/jbc.272.20.13242
|View full text |Cite
|
Sign up to set email alerts
|

Murine SR-BI, a High Density Lipoprotein Receptor That Mediates Selective Lipid Uptake, Is N-Glycosylated and Fatty Acylated and Colocalizes with Plasma Membrane Caveolae

Abstract: The class B, type I scavenger receptor, SR-BI, was the first molecularly well defined cell surface high density lipoprotein (HDL) receptor to be described. It mediates transfer of lipid from HDL to cells via selective lipid uptake, a mechanism distinct from receptor-mediated endocytosis via clathrin-coated pits and vesicles. SR-BI is expressed most abundantly in steroidogenic tissues (adrenal gland, ovary), where trophic hormones coordinately regulate its expression with steroidogenesis, and in the liver, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
283
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(308 citation statements)
references
References 88 publications
(81 reference statements)
20
283
0
Order By: Relevance
“…Taking into account the colocalization of SRBI and CAV1, 34 this indicates enhanced HDL cholesteryl ester uptake in the gallstone-susceptible strain.…”
Section: Body Weight Liver Weight Hepatic Cholesterol Content Andmentioning
confidence: 99%
“…Taking into account the colocalization of SRBI and CAV1, 34 this indicates enhanced HDL cholesteryl ester uptake in the gallstone-susceptible strain.…”
Section: Body Weight Liver Weight Hepatic Cholesterol Content Andmentioning
confidence: 99%
“…Although numerous studies have revealed many steps involved in LDL metabolism, significantly less is known about HDL metabolism. Novel insights concerning the metabolism of HDL have come from a recent series of experiments suggesting that the scavenger receptor class B type I (SR-BI) is an HDL receptor (3)(4)(5)(6)(7)(8)(9). SR-BI, a member of the CD36 superfamily, was originally cloned as a receptor for modified LDL (10 -12).…”
mentioning
confidence: 99%
“…For cxample, on hulnan thyroglobulin, 16 ()tit of the 20 putativc sites for .\~g13 cosylation havc been confirmed as being carbohydrate-bearing sites [30]. It has also been shown that routine SR-BI, a high-density lipoprntcin rcccptor that mediates selcctivc lipid uptake, is highl T N-glycosylated with multiple oligomannose chains [31].…”
Section: New Protein Glycosylation Sitesmentioning
confidence: 98%